2010
DOI: 10.1007/s00213-010-2143-x
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking adenylyl cyclase type 5 (AC5) show increased ethanol consumption and reduced ethanol sensitivity

Abstract: These results suggest that AC5 is an important signaling molecule regulating alcohol sensitivity and preference in animals. These data provide critical information for AC5 activation as a candidate target for the treatment of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Conversely, inhibition of PKA prior to ethanol administration decreased loss of righting reflex duration (Lai et al, 2007) and withdrawal-induced anxiety . Studies utilizing mutant mouse lines with reduced PKA activity mimic results found with pharmacological inhibition of PKA (Thiele et al, 2000;Naassila et al, 2002;Kim et al, 2011). The precise role of PKA in mediating these behaviors is complex, however, as some studies have found increased ethanol sensitivity in animals with diminished PKA activity (Wand et al, 2001;Yang et al, 2003;Maas et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, inhibition of PKA prior to ethanol administration decreased loss of righting reflex duration (Lai et al, 2007) and withdrawal-induced anxiety . Studies utilizing mutant mouse lines with reduced PKA activity mimic results found with pharmacological inhibition of PKA (Thiele et al, 2000;Naassila et al, 2002;Kim et al, 2011). The precise role of PKA in mediating these behaviors is complex, however, as some studies have found increased ethanol sensitivity in animals with diminished PKA activity (Wand et al, 2001;Yang et al, 2003;Maas et al, 2005).…”
Section: Discussionmentioning
confidence: 78%
“…This is a very important finding in view of the fact that LND also comprises extrapyramidal motor problems (Nyhan 1997;Jinnah and Friedmann 2000;Torres et al 2012). Moreover, AC5 is involved in alcohol drinking behavior and stress responses (Kim and Han 2009;Kim et al 2011), pointing to a central role of this AC isoform in CNS function.…”
Section: Discussionmentioning
confidence: 90%
“…Also, mice with genetic deletion of both adenylyl cyclase 1 (AC1) and AC8 exhibited decreased ethanol consumption and enhanced sensitivity to ethanol sedation (Maas et al, 2005). In contrast, mice lacking AC5 showed increased ethanol consumption and preference and reduced sensitivity to ethanol sedation (Kim et al, 2011). …”
Section: Discussionmentioning
confidence: 99%